2010
DOI: 10.1093/qjmed/hcq082
|View full text |Cite
|
Sign up to set email alerts
|

Lactose malabsorption and intolerance: a systematic review on the diagnostic value of gastrointestinal symptoms and self-reported milk intolerance

Abstract: Our review shows that high-quality studies on the diagnosis of lactose malabsorption and intolerance in primary care are urgently needed. An important prerequisite would be to clearly define the concept of lactose intolerance, as well as how it should be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 36 publications
1
87
1
4
Order By: Relevance
“…Ebben segíthetnek a kérdőívek. Kontrollált tanulmányokban észlelték, hogy a típusos tü-netek alapján az LI az esetek 80%-ában biztonsággal kór-ismézhető [27,28].…”
Section: Noninvazív Módszerekunclassified
“…Ebben segíthetnek a kérdőívek. Kontrollált tanulmányokban észlelték, hogy a típusos tü-netek alapján az LI az esetek 80%-ában biztonsággal kór-ismézhető [27,28].…”
Section: Noninvazív Módszerekunclassified
“…7 The symptoms of lactose intolerance result from bacterial fermentation of undigested lactose in the colon. Lactose intolerance can be diagnosed by having individuals ingest a standard dose of lactose after fasting and finding elevated levels of breath hydrogen which is produced by bacterial fermentation of undigested lactose in the colon.…”
Section: Diagnosing Lactose Intolerancementioning
confidence: 99%
“…Lactose intolerance can be diagnosed by having individuals ingest a standard dose of lactose after fasting and finding elevated levels of breath hydrogen which is produced by bacterial fermentation of undigested lactose in the colon. 4 A recent systematic review by Jellema et al 7 found that the diagnostic performance of reported symptoms that are associated with lactose intolerance (diarrhoea, abdominal pain, bloating and flatulence) was highly variable. More firm associations were found for ethnicity.…”
Section: Diagnosing Lactose Intolerancementioning
confidence: 99%
See 2 more Smart Citations